Merkel cell polyomavirus small tumour antigen activates the p38 MAPK pathway to enhance cellular motility. Issue 14 (31st July 2020) - Dobson, Samuel J.; Anene, Anthony; Boyne, James R.; Mankouri, Jamel; Macdonald, Andrew; Whitehouse, Adrian
Abstract : Merkel cell carcinoma (MCC) is an aggressive skin cancer with high rates of recurrence and metastasis. Merkel cell polyomavirus (MCPyV) is associated with the majority of MCC cases. MCPyV-induced tumourigenesis is largely dependent on the expression of the small tumour antigen (ST). Recent findings implicate MCPyV ST expression in the highly metastatic nature of MCC by promoting cell motility and migration, through differential expression of cellular proteins that lead to microtubule destabilisation, filopodium formation and breakdown of cell–cell junctions. However, the molecular mechanisms which dysregulate these cellular processes are yet to be fully elucidated. Here, we demonstrate that MCPyV ST expression activates p38 MAPK signalling to drive cell migration and motility. Notably, MCPyV ST-mediated p38 MAPK signalling occurs through MKK4, as opposed to the canonical MKK3/6 signalling pathway. In addition, our results indicate that an interaction between MCPyV ST and the cellular phospatase subunit PP4C is essential for its effect on p38 MAPK signalling. These results provide novel opportunities for the treatment of metastatic MCC given the intense interest in p38 MAPK inhibitors as therapeutic agents.